Pengaruh Kontrol Psikologis Orang Tua dan Kontrol Diri terhadap Perilaku Cyberbullying Remaja - Damayanti, Adinda Putri; Alfiasari; Islamiah, Nur (Jurnal Online Psikogenesis, 2024)
Cyberbullying is a deliberate, aggressive behavior perpetrated by individuals or groups through electronic contact against vulnerable victims. This study aims to analyze the effect of parental psychological control and adolescent self-control on cyberbullying behavior among adolescents. Employing explanatory research design with quantitative methods, the study utilized voluntary sampling to recruit adolescents aged 15-18 years who actively use social media and still reside with both parents in Bogor Regency. Data analysis included descriptive analysis, correlation testing, and multiple linear regression. The findings revealed a negative correlation between parental psychological control and adolescent self-control and a positive correlation between paternal and maternal psychological control. Additionally, the regression test indicated that parental psychological control, particularly in the form of personal attacks, significantly cyberbullying behavior. Furthermore, adolescents with low self-control demonstrated a higher likelihood of engaging in cyberbullying behavior.